Risk Factors of Immune-Mediated Hepatotoxicity Induced by Immune Checkpoint Inhibitors in Cancer Patients: A Systematic Review and Meta-Analysis - Ying Jiang; Ranyi Li; Xiaoyu Li; Ningping Zhang (Current Oncology)
Immune checkpoint inhibitors (ICIs) significantly improve survival, while immune-mediated hepatotoxicity (IMH) has been reported. To evaluate the incidence and potential risk factors of IMH among cancer patients treated by ICIs, PubMed/Medline, Web of Science, Cochrane, and Embase were searched before 30 March 2024 for systematic review and meta-analysis. Odds ratios (ORs) with 95% confidence intervals (CI) were calculated. Quality assessment was completed using the Newcastle–Ottawa scale. Of 1217 articles identified, 24 consisting of 9076 patients were included, with one study being prospective and the rest retrospective. The overall incidence of any grade IMH and grade ≥ 3 secondary to ICIs was 14% and 7%, respectively. The cholestatic pattern was more prevalent than the hepatocellular and mixed patterns. The meta-analysis revealed that ICI treatment was related to reduced risk of IMH in older patients (SMD: −0.18; 95% CI: −0.33 to −0.04), individuals with higher body mass index (WMD: −2.15; 95% CI: −3.92 to −0.38), males (OR: 0.44; 95% CI: 0.27 to 0.72), and patients with lung cancer (OR: 0.58, 95%CI 0.41 to 0.83). On the other hand, patients with liver metastasis (OR: 1.80; 95% CI: 1.47 to 2.20), history of ICI treatment (OR: 3.09; 95% CI: 1.21 to 7.89), diabetes (OR: 2.19; 95% CI: 1.36 to 3.51), chronic HBV (OR: 3.06; 95% CI: 1.11 to 8.46), and concomitant use of ICIs (OR: 8.73; 95% CI: 2.41 to 31.59) increased the risk of developing IMH. This study will provide clinicians with information on potentially high-risk groups for IMH, who need to be cautiously monitored for liver function when receiving immunotherapy.